Creating a demand for educational research : research learning in continuing teacher education - Allyson Macdonald (2008)
Fyrirlestur haldinn á „Den 10. nordiske læreruddannelseskongres” sem haldin var í Kennaraháskóla Íslands 21.-24. maí 2008 One aspect of belonging to a profession is that members of the profession have and use opportunities to renew their knowledge and skills at regular intervals. For the teaching profession there are several sources of knowledge, such as knowledge gained within the workplace, knowledge promoted in the activities of professional associations such as publications and conferences and knowledge created by educational researchers, often in cooperation with teachers. The purpose of this paper is to report on some results from an evaluation of educational research in Iceland carried out in 2003-2005 (Icelandic Centre, 2005). There was a mismatch between what was being produced and for whom, and what was being used and by whom. These results were unsettling and several initiatives have been undertaken in order to discuss and address these results. Here I will look at the role that continuing and/or graduate studies in education might have in addressing the mismatch, and will suggest that aspects of professionalism provide educational research with criteria of what might be marketable research.